Role of the South Pacific Convergence Zone in West Antarctic Decadal Climate Variability. Issue 12 (20th June 2019) - Clem, Kyle R.; Lintner, Benjamin R.; Broccoli, Anthony J.; Miller, James R.
Abstract: Regional atmospheric circulation along coastal West Antarctica associated with the Amundsen Sea Low (ASL) mediates ice shelf melt that governs Antarctica's contribution to global sea level rise. In this study, the South Pacific Convergence Zone (SPCZ) is identified as a significant driver of ASL variability on decadal time scales. Using the Community Earth System Model, we impose a positive sea surface temperature anomaly in the SPCZ that reproduces an increase in convective rainfall in the southwest SPCZ that has been observed in recent decades, consistent with the negative phase of the Interdecadal Pacific Oscillation (IPO). Many of the major climate shifts across West Antarctica during the 2000‐2014 period when the IPO was negative can be explained via a teleconnection over the ASL emanating from the SPCZ. Knowledge of these relationships significantly enhances our understanding and interpretation of past and future West Antarctic climate variability. Plain Language Summary: Heavy convective rainfall in the South Pacific Convergence Zone (SPCZ) alters the regional atmospheric circulation along coastal West Antarctica, impacting the regional climate and potentially driving warm ocean water upwelling that melts ice shelves. Increases in SPCZ rainfall cause cooling on the Antarctic Peninsula and warming across the Ross Ice Shelf and portions of East Antarctica. Such conditions were observed during the 2000‐2014 period in which the phase of the Interdecadal Pacific Oscillation, a naturally occurring mode of tropical Pacific decadal variability, was negative. The influence of the SPCZ on West Antarctic climate is consistent with observed shifts in West Antarctic climate over the period 2000‐2014. Therefore, the SPCZ, though a tropical climate feature, is found to be an important driver of West Antarctic climate on decadal time scales governed by the Interdecadal Pacific Oscillation. Key Points: Decadal variability in SST and precipitation along the poleward edge of the SPCZ is coherent with the Interdecadal Pacific Oscillation (IPO) The IPO influence on West Antarctic climate is in part tied to a SPCZ teleconnection to the Amundsen Sea Low (ASL) Enhanced rainfall in the SPCZ, consistent with the negative IPO phase, cools the Antarctic Peninsula and warms the Ross Ice Shelf and East Antarctica